Current State Analysis of Counterfeit Medicine Detection in Pharmaceutical Supply Chains in Pakistan - Imran Ahmad; Dr. Muhammad Umar (Spectrum of Engineering Sciences, 2025)
Counterfeit medicines are a serious challenge in Pakistan's pharmaceutical supply chain, posing a serious threat to public health and economic stability, as well as the credibility of the health care system as a whole. This paper discusses the current status of counterfeit medicine detection mechanisms in Pakistan by using qualitative methods like an interview with industry leadership. The study deals with the examination of the present legacy systems; prevalence and effect of counterfeit medicines; and a gap in rules and technology that needs to be filled. Urgent need: modern technological integration, updated regulation frameworks, strategic solutions to overcome the growing danger of counterfeit drugs.